New Finding on Zakat Efficiency Measurement in Indonesia 2016-2022 - Mimma Maripatul Uula; Nun Maziyyah (Islamic Social Finance, 2023)
This research aims to measure the efficiency of zakat amil institutions in Indonesia using the Data Envelopment Analysis (DEA) method for the 2016-2022 research period. The research objects used were 21 zakat institutions in Indonesia. The data from this research comes from the annual financial reports of each institution for the 2016-2022 period. The input variables in this research are employee costs, operational costs and total assets. And the output variable is the collection and distribution of zakat. The results of this research explain that during the 2016-2022 period, the level of efficiency of zakat institutions in Indonesia has a fluctuating trend from year to year and tends to increase. Based on the average efficiency score, it can be concluded that no zakat institution in Indonesia has reached the maximum level of efficiency. Furthermore, the Covid-19 pandemic has an impact on the efficiency level of Zakat Institutions. Then, the potential improvement analysis shows that the collection and distribution of zakat is the variable that causes the biggest inefficiency in zakat institutions. The results of the benchmarking analysis concluded that BMM and DD zakat institutions were the institutions with the most referrals.